Solvothermal growth of moiré superlattices in antimony telluride spiral-type nanoplates - Link, Robert; Marcus, Gabriel; Carroll, David (Frontiers in Materials, 2022)
The study of moiré superlattices (MSLs) has surged in recent years, as they have been found to host several emergent quantum phenomena associated with high electron correlations. In this study, we put forward a viable chemical route to the formation of moiré patterns in antimony telluride (Sb2Te3) nanoplates by leveraging screw dislocation-driven growth. These Sb2Te3 MSLs are synthesized using a scalable, one-pot, colloidal solution-liquid-solid (SLS) procedure. We report twist angles up to 0.52° (estimated using a combination of transmission electron microscope (TEM) image analysis and computer simulation). We investigate the early growth stages of Sb2Te3 spiral-type nanoplates under TEM, and we detail the growth of Sb2Te3 spiral-type nanoplates that feature a central nanopore, caused by tandem growth with nanorods. We hope that these methods will facilitate future investigation into the electronic properties of Sb2Te3 MSLs.